2016
DOI: 10.1158/1055-9965.epi-15-0756
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment and Insurance on Socioeconomic Disparities in Survival after Adolescent and Young Adult Hodgkin Lymphoma: A Population-Based Study

Abstract: Background Previous studies documented racial/ethnic and socioeconomic disparities in survival after Hodgkin lymphoma (HL) among adolescents and young adults (AYAs), but did not consider the influence of combined-modality treatment and health insurance. Methods Data for 9,353 AYA patients aged 15–39 when diagnosed with HL during 1988–2011 were obtained from the California Cancer Registry. Using multivariate Cox proportional hazards regression, we examined the impact of socio-demographic characteristics (race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 41 publications
3
91
0
1
Order By: Relevance
“…marital status, race/ethnicity, and neighborhood SES) are considered and is apparent for each of the eleven most common AYA cancers. Given that the small percentage of AYA cancer patients who were uninsured likely reflect retroactive enrollment in Medicaid at the time of cancer diagnosis [8, 13, 14], we considered publicly insured and uninsured together in the survival analyses. A number of factors related to healthcare access may mediate associations of no or public insurance with survival; including stage at diagnosis, delays in treatment receipt, details of treatment receipt and completion, Medicaid provider restrictions, or availability of information and support services among patients and survivors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…marital status, race/ethnicity, and neighborhood SES) are considered and is apparent for each of the eleven most common AYA cancers. Given that the small percentage of AYA cancer patients who were uninsured likely reflect retroactive enrollment in Medicaid at the time of cancer diagnosis [8, 13, 14], we considered publicly insured and uninsured together in the survival analyses. A number of factors related to healthcare access may mediate associations of no or public insurance with survival; including stage at diagnosis, delays in treatment receipt, details of treatment receipt and completion, Medicaid provider restrictions, or availability of information and support services among patients and survivors.…”
Section: Discussionmentioning
confidence: 99%
“…As in previous AYA studies [11, 13, 24, 25], insurance type was categorized as private/military (private insurance managed care, health maintenance organization, or preferred provider organization; private Insurance Fee-for-Service; military; Veterans Affairs; Tricare; or insurance, not otherwise specified), public/none (Medicaid, Medicare, Indian/Public Health Service, county funded not otherwise specified, not insured, not insured self-pay), and unknown. Consistent with prior observations that the small percentage of AYA cancer patients who were uninsured likely reflect retroactive enrollment in Medicaid at the time of cancer diagnosis [8, 13, 14], we considered publicly insured and uninsured together in the survival analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…222 An analysis of 9,353 AYA patients with HL showed that having either public or no health insurance was associated with poorer HL-specific survival compared with patients with private or military insurance (HR, 2.08; 95% CI, 1.52-2.84). 223 Furthermore, unemployment and lack of health insurance appear to be significant predictors of psychological distress in the childhood cancer survivor population. 224 Uninsured AYA patients are also less likely to participate in clinical trials.…”
Section: Socioeconomic Issuesmentioning
confidence: 99%